Hospital Episodes Due to Antidepressant Overdose: An Under-Utilised Source of Pharmacovigilance Data - MJ, Cooke; D, Tomlinson; G, Kitching; WS, Waring (Journal of Advanced Pharmaceutical Science And Technology, 2013)
Background: Antidepressant agents are commonly implicated in drug overdose, and the toxicological profile varies between agents. Clinical data concerning overdoses are not systematically sought or evaluated in pharmacovigilance. The present study sought to examine the feasibility of collecting Emergency Department data concerning antidepressant overdose. Methods : Presentations to York Hospital due to intentional antidepressant overdose were studied between 2010 and 2011. Data collected were the type of antidepressant, dose, co-ingested drugs, duration of hospital stay, and need for critical care. Community National Health Service prescription data were evaluated across York and North Yorkshire region. Results : There were 250 overdose episodes. These involved a selective serotonin reuptake inhibitor (SSRI) in 183 (73.2%), and a tricyclic in 45 (18.0%), equivalent to 24 episodes per 100,000 prescription items (95% CI 21-28 per 100,000) and 11 per 100,000 (8-15 per 100,000) respectively (P<0.0001). Citalopram was the most commonly prescribed, and associated with 22 overdose episodes per 100,000 (17-27 per 100,000). Fluoxetine was associated with 32 overdose episodes per 100,000 (24-41 per 100,000) (P=0.032 versus citalopram), whereas the lower rates were observed for amitriptyline (13, 9-17 per 100,000) (P=0.004) and dosulepin (2, 0-10 per 100,000) (P=0.001). Conclusions : A higher than expected number of overdose episodes involved an SSRI based on National Health Service primary care prescribing, and fewer episodes involved a tricyclic antidepressant. Clinical outcomes differed between agents, indicating the feasibility of using Emergency Department data to detect different patterns of toxicity between antidepressants. Further work is required to examine whether systematic collection of clinical toxicology data might enhance existing pharmacovigilance systems.
Keywords: Antidepressant; drug safety; overdose; pharmacovigilance; prescribing patterns; SSRI; toxicology; tricyclicantidepressant